Hubungan Antara Gen MTHFR C677T dan Skizofrenia - Nyak Intan Fadhilati; Juwita Saragih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Schizophrenia is a severe neuropsychiatric disorder that affects approximately 1% of the population, and is characterized by serious impairments in cognition, emotion and social functioning. The MTHFR gene is a key enzyme in folic acid metabolism, which plays an important role in biochemical processes in the body. One of the common genetic polymorphisms in MTHFR is C677T (rs1801133). Relevant articles were searched through an electronic database, Google Scholar, using the keywords “Relationship Between MTHFR C677T Gene and Schizophrenia”. MTHFR C677T can affect homocysteine metabolism, which in turn can affect the production of brain neurotransmitters such as dopamine and serotonin. An imbalance of these neurotransmitters has long been associated with schizophrenia. Environmental factors, such as stress, trauma, and social factors, also play an important role in the development of mental disorders, along with genetic factors such as MTHFR C677T.